Ultrasound Combined with Core Cross-Linked Nanosystem for Enhancing Penetration of Doxorubicin Prodrug/Beta-Lapachone into Tumors - Li Q (Dove Medical Press, 2020)
Qianyan Li,1 Wei Hou,1 Meixuan Li,1 Hemin Ye,1 Huanan Li,1 Zhibiao Wang1,2 1State Key Laboratory of Ultrasound in Medicine and Engineering, College of Biomedical Engineering, Chongqing Medical University, Chongqing 400016, People’s Republic of China; 2Chongqing Key Laboratory of Biomedical Engineering, Chongqing Medical University, Chongqing 400016, People’s Republic of ChinaCorrespondence: Huanan Li; Zhibiao WangState Key Laboratory of Ultrasound in Medicine and Engineering, College of Biomedical Engineering, Chongqing Medical University, 1 Yixueyuan Road, Yuzhong District, Chongqing 400016, People’s Republic of ChinaTel/ Fax +86 023 68485021Email 102733@cqmu.edu.cn; wangzb@cqmu.edu.cnBackground: Nanosized drug delivery systems (NDDSs) have shown excellent prospects in tumor therapy. However, insufficient penetration of NDDSs has significantly impeded their development due to physiological instability and low passive penetration efficiency.Methods: Herein, we prepared a core cross-linked pullulan-modified nanosized system, fabricated by visible-light-induced diselenide bond cross-linked method for transporting β-Lapachone and doxorubicin prodrug (boronate-DOX, BDOX), to improve the physiological stability of the NDDSs for efficient passive accumulation in tumor blood vessels (β-Lapachone/BDOX-CCS). Additionally, ultrasound (US) was utilized to transfer β-Lapachone/BDOX-CCS around the tumor vessel in a relay style to penetrate the tumor interstitium. Subsequently, β-Lapachone enhanced ROS levels by overexpressing NQO1, resulting in the transformation of BDOX into DOX. DOX, together with abundant levels of ROS, achieved synergistic tumor therapy.Results: In vivo experiments demonstrated that ultrasound (US) + cross-linked nanosized drug delivery systems (β-Lapachone/BDOX-CCS) group showed ten times higher DOX accumulation in the tumor interstitium than the non-cross-linked (β-Lapachone/BDOX-NCS) group.Conclusion: Thus, this strategy could be a promising method to achieve deep penetration of NDDSs into the tumor.Keywords: nanosized drug delivery system, core cross-linked, physiological stability, ultrasound, deep tumor penetration